Mobile phone adoption and appropriation in Malaysia and the contribution of age and gender - Abdul Karim, Nor Shariza; Alias, Rose Alinda; Mokhtar, Shamsul Anuar; Abdul Rahim, Nor Zairah (2009)
This study investigates the adoption and appropriation of mobile phone technologies by building on the technology adoption and appropriation theories on different age group and gender in the Malaysian society. In order to achieve the objectives of the study, a nationwide survey using computer assisted telephone interviews (CATI) was conducted on 1710 randomly selected mobile phone users in Malaysia. The result of the study allows us to describe important elements of mobile phone appropriation in Malaysia and explore the influence of individual characteristics such as gender and age on different patterns of mobile phone use. The results of the study are expected to assist in understanding the use of mobile phone across different cohort groups in the society, particular those in different age group and gender, and serve as a mechanism in guiding the development of mobile phone applications and design by service providers and manufacturers respectively; as well as in aiding policy formulation on mobile phone use at the work place or school.